Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Kinerja Karyawan Generasi Z: Peran Mediasi Employee Engagement di Era Kerja Hybrid - Daryoto Mulyadi Candra (EBISMAN eBisnis Manajemen, 2025)
This study aims to analyze the influence of emotional intelligence and spiritual intelligence on the performance of Generation Z employees, with employee engagement as a mediating variable in the hybrid work era. The phenomenon of changing work patterns due to technological developments and the global pandemic has created a new work model that demands adaptive skills and emotional and spiritual balance within individuals. Generation Z, known for being technologically savvy but prone to digital fatigue, requires internal support in the form of emotional and spiritual intelligence to increase work engagement and optimal performance. This research method used a quantitative approach, collecting data through questionnaires from 120 Generation Z employees in various industrial sectors implementing a hybrid work system. Data analysis was conducted using Structural Equation Modeling (SEM). The results showed that emotional intelligence and spiritual intelligence have a significant positive effect on employee engagement and performance. Furthermore, employee engagement was shown to mediate the relationship between these two forms of intelligence and performance. These findings emphasize the importance of developing emotional and spiritual dimensions in human resource management to address the dynamics of the modern workplace.